Bearing fault detection and fault size estimation using fiber-optic sensors. (1st April 2019) - Alian, Hasib; Konforty, Shlomi; Ben-Simon, Uri; Klein, Renata; Tur, Moshe; Bortman, Jacob
Highlights: Pioneering research on diagnostics of bearings by strain measured using FBG fiber optical sensors. Optical sensors provide accurate estimates of the spall-like faults in both the outer and inner races. Extensive experiments were conducted on two different test rigs with different bearings. Moreover, naturally developed faults in an endurance test was presented. Abstract: Health monitoring of rotating machinery is commonly based on vibration signals. Instead, this pioneering research provides bearing diagnostics using strain measurements, obtained from Fiber Bragg Grating (FBG) fiber-optic sensors. Besides detection of the damage via spectral data, these optical sensors also allow the estimation of damage severity through the direct and accurate measurement of the damage size of small spalls in the bearing races, an essential capability for the prognosis of remaining useful life. FBG sensors are small and can be easily placed in the immediate proximity of the bearing or even embedded inside it, thereby ensuring much enhanced signal-to-noise ratio through the minimizing transmission path effects from remote disturbances. These ball-bearing related diagnostic capabilities of FBG sensors are demonstrated via seeded tests, as well as by means of extended monitoring of bearings during fatigue endurance tests. Sensitivity to FBG sensor location is studied, showing acceptable values at all housing measuring points around the bearing. Fiber-optic sensors appear to have promising diagnostic potential for spall-like faults in both the outer and inner races of ball bearings with a very good discrimination power.